Evaluation of patients' awareness regarding proper maintenance of removable partial prostheses - Sara Mogharrabi; Safoura Ghodsi; Majed Kooti; Asadallah Ahmadzadeh; Neshatafarin Manouchehri (Tehran University of Medical Sciences, 2021)
Background and Aims: Removable partial denture (RPD) is a common treatment to restore partially edentulous areas; however, a limited number of studies have been made on oral hygiene habits among patients with RPD. The aim of this study was to evaluate the patients' knowledge about various cleaning methods of RPD to consciously improve hygienic habits of the patients. Materials and Methods: This study was a cross-sectional study performed on 96 RPD patients referred to Jundishapur faculty of dentistry from 1395 to 1396. Demographic data namely age, sex, level of education, and other information about general health status, duration of dentures usage, and denture cleaning frequency were taken by the census through questionnaires. The descriptive statistics, chi-square, and T-test were used for statistical analysisof data (P<0.05). Results: The patient age, sex, and smoking habits had significant effects on the prosthesis maintenance habits (P<0.05). The patients over 50 years of age, females, and nonsmokers significantly preferred dipping method over other RPD storage methods (P<0.05). The frequency of denture cleaning was significantly greater in males (53.3%) compared to females (23.9%) (P<0.05). Conclusion: According to the results of this study, most RPD patients did not clean their dentures appropriately and have little knowledge on how to maintain and clean them. Regular and periodic recall and written instructions might be helpful to improve patientschr('39') awareness on proper cleaning and maintenance of partial dentures.